A first assessment of the impact of the extreme 2018 summer drought on Central European forests - Schuldt, Bernhard; Buras, Allan; Arend, Matthias; Vitasse, Yann; Beierkuhnlein, Carl; Damm, Alexander; Gharun, Mana; Grams, Thorsten E.E.; Hauck, Markus; Hajek, Peter; Hartmann, Henrik; Hiltbrunner, Erika; et al. (Basic and applied ecology, 2020)
In 2018, Central Europe experienced one of the most severe and long-lasting summer drought and heat wave ever recorded. Before 2018, the 2003 millennial drought was often invoked as the example of a “hotter drought”, and was classified as the most severe event in Europe for the last 500 years. First insights now confirm that the 2018 drought event was climatically more extreme and had a greater impact on forest ecosystems of Austria, Germany and Switzerland than the 2003 drought. Across this region, mean growing season air temperature from April to October was more than 3.3°C above the long-term average, and 1.2°C warmer than in 2003. Here, we present a first impact assessment of the severe 2018 summer drought and heatwave on Central European forests. In response to the 2018 event, most ecologically and economically important tree species in temperate forests of Austria, Germany and Switzerland showed severe signs of drought stress. These symptoms included exceptionally low foliar water potentials crossing the threshold for xylem hydraulic failure in many species and observations of widespread leaf discoloration and premature leaf shedding. As a result of the extreme drought stress, the 2018 event caused unprecedented drought-induced tree mortality in many species throughout the region. Moreover, unexpectedly strong drought-legacy effects were detected in 2019. This implies that the physiological recovery of trees was impaired after the 2018 drought event, leaving them highly vulnerable to secondary drought impacts such as insect or fungal pathogen attacks. As a consequence, mortality of trees triggered by the 2018 events is likely to continue for several years. Our assessment indicates that many common temperate European forest tree species are more vulnerable to extreme summer drought and heat waves than previously thought. As drought and heat events are likely to occur more frequently with the progression of climate change, temperate European forests might approach the point for a substantial ecological and economic transition. Our assessment also highlights the urgent need for a pan-European ground-based monitoring network suited to track individual tree mortality, supported by remote sensing products with high spatial and temporal resolution to track, analyse and forecast these transitions.